Gamma-range oscillations evoked by Optogenetic stimulation - an in silico study - Malekzadeh, Meriam; Giugliano, Michele (Student Undergraduate Research E-journal!, 2019)
Gamma-range oscillations are repetitive neuronal activation in various regions of the brain, displaying prominent energy distribution in the 30-90 Hz frequency band. It is shown that these oscillations emerge through excitatory-inhibitory neuronal interplay, but their mechanisms and functions remain unknown. Therefore, it is necessary to simplify the in vivo complexity. This has been accomplished by the host laboratory, which reproduced these rhythms in an in vitro model of cortical microcircuitry using Optogenetic tools and suggested a simple firing-rate mathematical model. Since Optogenetics influences synaptic efficacy, I propose an extension of this mathematical model by dynamical properties of synaptic transmission.